Application time affects synthetic auxins herbicides in tank-mixture with paraquat on hairy fleabane control - Ruy Orsolin da Silva, Diecson; Moraes de Aguiar, Adalin Cezar; Basso, Claudir José; Schmidt Muraro, Dionei (Revista Ceres, 2025)
Conyza sp. was the first glyphosate-resistant weed in Brazil’s soybean crop. Synthetic auxin herbicides followed by paraquat has improved the hairy fleabane control, and time of day of herbicide application can affect the control efficacy. There are no studies reporting the effects of the application time of synthetic auxins in tank-mixture with paraquat, or in sequential application with paraquat at two growth stages of hairy fleabane, applied at different times of the day. The herbicides were sprayed during the morning and night. 2,4-D applied alone was more effective applied during the day, while dicamba efficiency was higher when applied at night in the rosette stage. The mixture of 2,4-D and paraquat was more efficient when applied during the night. Tall hairy fleabane were more effectively controlled by dicamba + paraquat as well as any synthetic auxin followed by paraquat. When herbicides were applied at night, efficiency was slightly higher.